الخطاب الاجتماعي في الرسم ما بعد الحداثي - المعموري، حمدية كاظم روضان (الجامعة المستنصرية - كلية التربية الأساسية, 2019)
يعد الخطاب الاجتماعي في الفن، نتاجا لتراكمات المعرفة الإنسانية والموروث الحضاري وكذلك الانفتاح والتقدم العلمي والتكنولوجي الذي بات جزءا من فنون ما بعد الحداثة وعبر نسيج التفاعل ما بين عموم الظواهر والممارسات وبين استحضار واستبدال وإحالة المفردات من واقعها المتداول إلى واقع جمالي جديد تكون فيه الظواهر الاجتماعية وآلياتها فاعلة في بناء الخطاب البصري. لذا تناول البحث الحالي (الخطاب الاجتماعي في الرسم ما بعد الحداثة) إذ درس الخطاب الاجتماعي فكريا وفلسفيا وجماليا ودوره في فنون الرسم وما بعد الحداثي وآليات اشتغاله في اتجاهات الرسم ما بعد الحداثي، ويتألف البحث الحالي من أربعة فصول وقد تضمن الفصل الأول من البحث تعريفا بمشكلة البحث والتي تحددت من خلال الإجابة على السؤال التالي: (ما هي سمات الخطاب الاجتماعي في الرسم ما بعد الحداثي) وأهمية البحث والحاجة إليه. أما هدف البحث فقد تم تحديده (بالتعرف على سمات الخطاب الاجتماعي في الرسم ما بعد الحداثي). وقد قامت الباحثة بتحديد أهم المصطلحات الواردة في البحث أما الفصل الثاني فقد أشتمل على مبحثين الأول يمثل مفهوم الخطاب الاجتماعي فكريا وفلسفيا. والمبحث الثاني فقد تناول الخطاب الاجتماعي في الرسم ما بعد الحداثي. أما الفصل الثالث فقد احتوى إجراءات البحث وتضمن، مجتمع البحث واختيار العينة وتحليلها والبالغة (5) نماذج. وقد اعتمد البحث المنهج الوصفي التحليلي عند تحليل العينة. وجاء الفصل الرابع بنتائج البحث والاستنتاجات فضلا عن التوصيات والمقترحات، ومن أبرز النتائج التي توصلت إليها الباحثة. 1. تكشف نتاجات فنون ما بعد الحداثة في سياقاتها عن هيمنة أنواع من الخطاب منه الاجتماعي والسياسي التي تمثل الدوافع الحقيقية لدى الفنان والمتلقي والتي تمثل انعكاسا للأوضاع الاجتماعية والاقتصادية في مجتمعات العولمة وما بعد الحداثة. 2. مثل الخطاب البصري التشكيلي لفنان ما بعد الحداثة، حالة اندماجية بين الظواهر الاجتماعية والبنى الفكرية والثقافية والاجتماعية والسياسية ... مما جعلها تشكل المكون الأساسي للكثير من نتاجاته الفنية. لذا امتازت صورها بكونها انعكاسات صادقة لتلك البنى. ومن الاستنتاجات 1. تعددت أنماط التعبير الفني بعد الحداثي بتغير اتجاهات وأفكار المبدعين الذين يعبرون عن مواقفهم من عالم السرعة والاستهلاك والإعلام العابر للثقافات.
The social discourse in the composition of the Arts, the result of the accumulation of human knowledge and cultural heritage, as well as openness and progress of scientific and technological, which has become part of the arts postmodernism and through the fabric of the interaction between the general phenomena and practices and between evoke and replacement referral vocabulary of reality rolling into reality and aesthetic new it be social phenomena operations and mechanisms effective in weaving the fabric of visual discourse. So Find the current intake (social discourse in the graphic post-modernist) as he studied social discourse intellectually and philosophically and aesthetically and its role in the graphic arts and post-modernist and how they functioned in the drawing directions postmodern, consisting current research from four chapters have been the first chapter of the research included a definition of the problem of search and identified by answering the following question: (what are the attributes of social discourse in drawing postmodern) and the importance of research and the need for it. The aim of the research has been defined (to identify the attributes of social discourse in drawing postmodern). The researcher analyzed the most important terms in the Find the second chapter included the first two sections representing the concept of social discourse intellectually and philosophically. The second topic dealt with. Social discourse in the post-modernist painting. The third chapter contains research procedures were included, the research community and the sampling and analysis of the (5) models. And adopted Find descriptive and analytical approach when analyzing the sample. The fourth quarter results of the research and conclusions as well as recommendations and proposals, and highlighted the findings of the researcher. 1. Products of arts reveal postmodernism in the contexts of the dominance of types of social and political discourse which represents the real motives of the artist and the receiver, which represent a reflection of the social and economic conditions in the communities of globalization and postmodernism of it. 2. Such as visual rhetoric visual artist postmodern state of fusion between social phenomena intellectual, cultural, social and political structures ... which made them constitute the main component of many technical Ntegath. So images characterized by being honest reflections of those structures. It Alastnajat 1-Varied modes of artistic expression postmodern change and ideas of the creators who express their positions from the world of speed, consumption and media cross-cultural trends. Find four chapters included care of the first chapter of which the methodological framework for the search represented "The problem of the search as well as the goal of a search (The second chapter included.
Keywords: الخطاب الاجتماعي -- القيم الجمالية -- فنانو ما بعد الحداثة -- الإبداعات الفكرية -- التعبيرات الفنية